STRATEGI KEBIJAKAN PENGEMBANGAN KAWASAN WISATA PANTAI MANGGAR KOTA BALIKPAPAN - Adi Wibowo; Adam Idris; Syahrani . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research was using SWOT analysis to consider internal and external factors that influenced the tourist development in Manggar region. The result showed that there were a need for strategic policy which include increasing interest in sports especially sports like, jetsky, parasailing; next was to build networks with other available objects in Manggar Beach nearby such as breeding crocodiles house, Ambalat Beach and Lamaru Beach; together with tour and travel agents both in Indonesia and overseas; and then tighten the relationship between district and central governments; and last, create a website for Manggar Coastal Ressort.